Mitigation of oxidative stress damage caused by abiotic stress to improve biomass yield of microalgae: a review - Zhu, Jiangyu; Cai, Yifei; Wakisaka, Minato; Yang, Zhengfei; Yin, Yongqi; Fang, Weiming; Xu, Yan; Omura, Taku; Yu, Ruihui; Zheng, Alvin Lim Teik (Elsevier, 2023)
Microalgae have been recognized as emerging cell factories due to the high value-added bio-products. However, the balance between algal growth and the accumulation of metabolites is always the main contradiction in algal biomass production. Hence, the security and effectiveness of regulating microalgal growth and metabolism simultaneously have drawn substantial attention. Since the correspondence between microalgal growth and reactive oxygen species (ROS) level has been confirmed, improving its growth under oxidative stress and promoting biomass accumulation under non-oxidative stress by exogenous mitigators is feasible. This paper first introduced ROS generation in microalgae and described the effects of different abiotic stresses on the physiological and biochemical status of microalgae from these aspects associated with growth, cell morphology and structure, and antioxidant system. Secondly, the role of exogenous mitigators with different mechanisms in alleviating abiotic stress was concluded. Finally, the possibility of exogenous antioxidants regulating microalgal growth and improving the accumulation of specific products under non-stress conditions was discussed.